The Protective Mechanism of Antioxidants in Cadmium-Induced Ototoxicity in Vitro and in Vivo - Kim, Su-Jin (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Several heavy metals have been shown to have toxic effects on the peripheral and central auditory system. Cadmium (Cd(2+)) is an environmental contaminant showing a variety of adverse effects. Given the current rate of release into the environment, the amount of Cd(2+) present in the human body and the incidence of Cd(2+)-related diseases are expected to increase. OBJECTIVE: The overall aim of this study was to gain further insights into the mechanism of Cd(2+)-induced ototoxicity. METHODS: Cell viability, reactive oxygen species (ROS), mitochondrial membrane potential (MMP), cytochrome c (cyt c), phosphorylated extracellular signal-regulated protein kinase (p-ERK), caspases, morphologic change, and functional changes in HEI-OC1 cells, rat cochlear explants, and mouse cochlea after Cd(2+) exposure were measured by flow cytometry, immunohistochemical staining, Western blot analysis, and auditory brainstem response (ABR) recording. Mechanisms underlying Cd(2+)ototoxicity were studied using inhibitors of different signaling pathways, caspases, and antioxidants. RESULTS: Cd(2+) exposure caused cell death, ROS generation, MMP loss, cyt c release, activation of caspases, ERK activation, apoptosis, and finally auditory threshold shift. Cd(2+) toxicity interfered with inhibitors of cellular signaling pathways, such as ERK and c-jun N-terminal kinase, and with caspase inhibitors, especially inhibitors of caspase-9 and caspase-3. The antioxidants N-acetyl-l-cysteine and ebselen showed a significant protective effect on the Cd(2+) toxicity. CONLCUSIONS: Cd(2+) is ototoxic with a complex underlying mechanism. However, ROS generation may be the cause of the toxicity, and application of antioxidants can prevent the toxic effect.